UTILIZATION OF NUTRIENTS IN COLLECTED HUMAN URINE FROM ECOSAN TOILET FOR ECO-FRIENDLY CROP PRODUCTION - G. SRIDEVI; C. A. SRINIVASAMURTHY; U.SURENDRAN (The Bioscan, 2019)
Studies were conducted to study the important of ecosan toilet in crop production. Human urine though have high nutrient value is being neglected and simply wasted. Out of the human excreta, urine has high nitrogenous fertilizer value than feces. ECOSAN toilet, it can be of great use in fulfilling the fertilizer demand of the country. Human urine is one of them, and has been gaining popularities as a raw material for crop cultivation. In general 3-6 splits urine application in addition with phosphorus and potash fertilizer gave the comparable result with that of chemical fertilizer The main objective of this review paper is to assess the effect of human urine on crop yield and to find out the appropriate urine dose and time of application to different crops.